2022
DOI: 10.1111/gove.12711
|View full text |Cite
|
Sign up to set email alerts
|

Critical thoughts about critical mass in representative bureaucracy: A theoretical exploration and empirical illustration

Abstract: Studies of representative bureaucracy frequently reference the need for a critical mass before an underrepresented group can influence policy outputs or outcomes, but the empirical literature is modest and presents mixed findings. This article presents a theoretical exploration to illustrate how critical mass can link individual behavior to organizational contexts. By examining both active representation and symbolic representation at both the individual and organizational level and specifying the different mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…Female representation in police is generally much lower than in other public institutions, including the South Korean Police of which only about 11% of the workforce is women. It falls short of the “critical mass” which prior studies have pointed out as a condition for active representation (e.g., see Meier & Xu, 2022). Considering that intimate partner violence is an area in policing where the patriarchal marginalization of women and gender power imbalance are reproduced (e.g., DeJong et al, 2008; Rowe & Macauley, 2018), our study highlights gender representation as a key initiative for police reform.…”
Section: General Discussion and Implicationsmentioning
confidence: 63%
“…Female representation in police is generally much lower than in other public institutions, including the South Korean Police of which only about 11% of the workforce is women. It falls short of the “critical mass” which prior studies have pointed out as a condition for active representation (e.g., see Meier & Xu, 2022). Considering that intimate partner violence is an area in policing where the patriarchal marginalization of women and gender power imbalance are reproduced (e.g., DeJong et al, 2008; Rowe & Macauley, 2018), our study highlights gender representation as a key initiative for police reform.…”
Section: General Discussion and Implicationsmentioning
confidence: 63%
“…The concept of critical mass suggests that an organization needs sufficient representation of female bureaucrats to bring about positive changes in the organizational culture and improve policy outcomes for female citizens (Hindera & Young, 1998). Although critical mass theory has mostly been used to explain the link between passive and active representation, scholars have recently suggested that it can also influence symbolic representation (Baniamin & Jamil, 2023; Meier & Xu, 2022), especially when individuals respond to aggregate levels of representation. In the current experimental context, the organization where female officers slightly outnumber male officers, compared to one where there are equal numbers of female and male officers, can be taken as a signal to female citizens that the organization has the capacity to respond more effectively to crimes against women.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the many discussions on active and symbolic representation (Bishu and Kennedy 2020;Keiser et al 2002;Kennedy 2014;Riccucci and Van Ryzin 2017), the theoretical logic behind contagion effects has not been developed even though there is some evidence of contagion effects (in education see Atkins and Wilkins 2013;Meier and Xu 2022; in the judiciary see Kastellec 2011; in law enforcement see Li 2021) and the processes has long been noted (see Meier, Wrinkle and Polinard 1999;Meier and Nicholson-Crotty 2006;Meier and Capers 2012). Empirically, there is also evidence in the literature that nonminority bureaucrats can adopt the role of acting as a minority representative (see Bradbury and Kellough 2008;Selden 1997), and the diversity management literature appears to describe a similar process of influence (Groeneveld and Meier 2022).…”
Section: Contagion Effects In Representative Bureaucracymentioning
confidence: 99%